2006
DOI: 10.1638/05-102.1
|View full text |Cite
|
Sign up to set email alerts
|

Blood Values in Free-Ranging Nesting Leatherback Sea Turtles (Dermochelys Coriacea) on the Coast of the Republic of Gabon

Abstract: Leatherback sea turtles (Dermochelys coriacea) are the most endangered of the seven species of sea turtles. The health status of leatherbacks is largely unknown, although the number of nesting females recorded throughout the world has decreased precipitously in the last few decades. Central African beaches may provide one of the last strongholds for nesting leatherback females. In the region, oil extraction and incidental capture pose significant threats to the health of the population. Physical examinations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
90
7
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(127 citation statements)
references
References 10 publications
29
90
7
1
Order By: Relevance
“…Values from this study are similar to values in nesting leatherback turtles, cholesterol (7.58 mmol/l6 1.89) and triglyceride (4.65 mmol/l6 0.40; Deem et al, 2006), but differs from previously published cholesterol (2.74 mmol/l) and triglyceride (0.98 mmol/l) values for free-ranging foraging loggerhead juvenile and adult turtles (Bolten et al, 1992), values similar to the foraging loggerheads in this study. The higher total protein, albumin, and globulin values for nesting females is also compatible with the reproductive state of turtles in this behavior (Harr et al, 2001;Campbell, 2004).…”
Section: Deem Et Al-blood Values In Loggerhead Turtlessupporting
confidence: 86%
“…Values from this study are similar to values in nesting leatherback turtles, cholesterol (7.58 mmol/l6 1.89) and triglyceride (4.65 mmol/l6 0.40; Deem et al, 2006), but differs from previously published cholesterol (2.74 mmol/l) and triglyceride (0.98 mmol/l) values for free-ranging foraging loggerhead juvenile and adult turtles (Bolten et al, 1992), values similar to the foraging loggerheads in this study. The higher total protein, albumin, and globulin values for nesting females is also compatible with the reproductive state of turtles in this behavior (Harr et al, 2001;Campbell, 2004).…”
Section: Deem Et Al-blood Values In Loggerhead Turtlessupporting
confidence: 86%
“…However, according to WILKINSON (2004), calcium is mobilized for egg formation during the reproductive period. DEEM et al (2006) also found elevated calcium and phosphorus levels in a population of nesting leatherbacks.…”
Section: Resultsmentioning
confidence: 79%
“…Pb, Hg, Cd and As) but significantly lower hepatic Fe levels compared with those indicated by (albeit scarce) existing data on Dermochelys coriacea (Davenport & Wrench 1990, Caurant et al 1999, Godley et al 1999, Deem et al 2006, Guirlet et al 2008, Innis et al 2010, Harris et al 2011. The data obtained for Se, Zn, Hg, Cd and Pb concentrations were also higher than those reported for loggerhead and green sea turtles from the Mediterranean area (Andreani et al 2008).…”
Section: Discussionmentioning
confidence: 70%